Expression of p16 and HPV E4 on biopsy samples and methylation of FAM19A4 and miR124‐2 on cervical cytology samples in the classification of cervical squamous intraepithelial lesions. (5th February 2020) - Leeman, Annemiek; Jenkins, David; del Pino, Marta; Ordi, Jaume; Torné, Aureli; Doorbar, John; Meijer, Chris J. L. M.; van Kemenade, Folkert J.; Quint, Wim G. V.
Abstract: The decision to treat a cervical squamous intraepithelial lesion (SIL) by loop electrosurgical excision procedure (LEEP) relies heavily on a colposcopy‐directed biopsy showing high‐grade (H)SIL. Diagnosis is often supported by p16, an immunohistochemical (IHC) biomarker of high‐risk (hr)HPV E7 gene activity. Additional potential markers include methylation of tumor suppressor genes FAM19A4/miR124‐2 in cervical cytology for advanced transforming HSIL and the IHC marker HPV E4 for productive, potentially regressing lesions. In 318 women referred for colposcopy, we investigated the relationship between staining patterns of p16 and E4 IHC in the worst biopsy, and the relation of these to FAM19A4/miR124‐2 methylation status in cytology. E4‐positive staining decreased with increasing SIL/CIN grade from 41% in LSIL to 3% in HSIL/CIN3. E4 positivity increased with grade of p16 when p16 expression was limited to the lower two third of the epithelium (r = 0.378), but fell with expression over. Loss of E4 expression in the worst lesion was associated with the methylation of FAM19A4/miR124‐2. We also examined whether these biomarkers can predict the histological outcome of the LEEP biopsy in a subgroup of 119 who underwent LEEP treatment. About 85% of women with ≥lower two third p16 staining/E4‐negative HSIL biopsies and 65% with limited p16 staining/E4‐positive HSIL biopsies had ≥HSIL in the LEEP specimen ( P  = .025). p16 expression in a biopsy is related both to viral production and transformation, while decreased E4 expression relates to methylation, indicating advanced HSIL. p16 expression in ≥2/3 of the epithelium and absent E4 indicate likely HSIL on a subsequent LEEP specimen. Abstract : We found an inverse relation between HPV E4 expression on biopsy and hypermethylation of FAM19A4/miR124‐2 on cytology sample. p16 and hypermethylation increased with the severity of the lesion and may be used to identify premalignant transformation. The use of p16/E4 immunostaining and methylation could offer valuable information beyond current grading practice.